The practice of citizenship : Black politics and print culture in the early United States - Spires, Derrick Ramon (University of Pennsylvania Press, 2019)
The Practice of Citizenship traces the parallel development of early black print culture and legal and cultural understandings of U.S. citizenship. Considering a variety of texts by both canonical and lesser-known authors, Derrick R. Spires demonstrates how black writers articulated an expansive, practice-based theory of citizenship